Determining the suitability of using eye wrinkle patterns for the accurate identification of individual black rhinos - Patton, Felix; Jones, Martin (Pachyderm, 2010)
Photograhic identification is used to identify individual black rhinos (Diceros bicornis) with the distinguishing features of sex, the size and shape of the anterior and posterior horns, peculiarities of the ears, the pattern of wrinkle contours on the snout, prominent scars and sores on the body, the state of the tail, body size including the size of a calf in relation to the mother and skin folds. Eye wrinkle patterns have received little attention but were found to be useful when separating a large number of photographs of 19 captive rhinos particularly for distinguishing individual sub-adults where other features such as horn length and shape were very similar. Each rhino was found to have unique eye wrinkle patterns which remained consistent when the eyes were open or closed. By developing and applying a series of tests, judgement errors that occur when reviewing eye wrinkle photographs were determined and are reported. Results show that individual black rhinos can be accurately identified from suitable photographs but, even for the best of the judges, using eye wrinkles alone to identify individual rhinos was not completely reliable. Key words: photo-identification, photographs, black rhinos L’identification photographique est utilisée à identifier différents rhinocéros noirs (Diceros bicornis) ayant des traits distinctifs de sexe, de taille et de la forme des cornes antérieure et postérieure, les particularités des oreilles, la configuration des contours des rides sur le museau, les cicatrices et les blessures sur le corps, l’état de la queue, la taille du corps - y compris celui d’un veau par rapport à sa mère - et les plis de la peau. Les configurations des rides oculaires ont suscité peu d’attention mais se sont avérés utiles quand on a organisé un grand nombre de photographies de dix-neuf rhinocéros captifs, surtout pour distinguer les différents sous-adultes alors que d’autres traits, comme la longueur et la forme de la corne, étaient semblables. Chaque rhinocéros s’est avéré avoir des configurations de rides oculaires qui restaient conformes que les yeux soient ouverts ou fermés. En développant et en appliquant une série de tests, les erreurs d’appréciation qui se produisent lorsqu’on examine les photographies des configurations des rides oculaires ont été déterminées et rapportées. Les résultats montrent qu’on peut correctement identifier les différents rhinocéros noirs à partir des photographies appropriées mais, même pour le meilleur des juges, les rides oculaires seules n’étaient pas complètement fiables pour identifier les individus.